Pengaruh Pemberian Kompres Hangat terhadap Penurunan Disminorea pada Remaja Putri di SMA Nurcahaya Medan - Purwaningsih, Purwaningsih; Sinuraya, Evamona; Jundapri, Kipa; Khairani, Ade Irma (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
Dysmenorrhea, characterized by cramping in the lower abdomen, varies in severity from mild to severe and is influenced by the duration of menstruation and the amount of menstrual blood (Husna, 2018). According to the World Health Organization, approximately 90% of women worldwide experience dysmenorrhea, with 10-15% suffering from severe cases. Non-pharmacological treatments, such as warm compresses, need to be developed. In Indonesia, 55% of women of reproductive age suffer from dysmenorrhea, which can be disruptive despite generally not being dangerous. The Indonesian Ministry of Health (2020) reported that 37% of students in Indonesia have experienced dysmenorrhea at school, with a national incidence rate of 64.25%, including 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. Over the past 50 years, it has been recorded that 75% of women experience menstrual pain, with primary dysmenorrhea symptoms usually occurring in women of reproductive age and those who have never been pregnant, and 61% of unmarried women affected (Syamsuryanita & Nurul Ikawati, 2020). This study aims to analyze the effect of warm compress application on reducing dysmenorrhea in adolescent girls. A quantitative pre-experimental design was employed, involving a one-group pretest-treatment-posttest approach. The population consisted of 30 students at Nurcahaya High School Medan, with a sample size determined using the Slovin formula. The results showed that before applying warm compresses, 23.33% of respondents reported a pain scale of 6, while after treatment, 23.3% reported a pain scale of 2. The average pain level decreased from 5.69 before treatment to 4.05 after treatment. The Wilcoxon test indicated a significant effect of warm compresses on reducing dysmenorrhea pain (Asymp.Sig < 0.05), with an average score difference of 1.64. In conclusion, warm compress therapy significantly reduces dysmenorrhea intensity in adolescents, evidenced by the shift from moderate to mild pain levels, supported by a significant level of 0.000 < 0.05.